Restoring function and performance in archers with rotator cuff injuries: The combined role of muscle energy technique and cryotherapy - Singh, A.; Mehta, S. (World Journal of Research and Review, 2025)
Background: Archery is a practice, which is highly repetitive and loaded massively on the upper extremities, which are asymmetrical. Although it may seem that the biomechanical requirements of the Draw and Hold phases of the sport are mild, they pose huge loads on the glenohumeral joint. The rotator cuff and especially the supraspinatus and infraspinatus tendons are vulnerable to overuse trauma, subacromial impaction and tendinopathy.